Survey of Nutrition Knowledge Level and Consumption Patterns In Futsal Athletes - Sasmarianto; Harisca, Nadyta; Meera bin Abdullah, Nagoor (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. The purpose of this study is to find out the level of knowledge about nutrition and food consumption patterns of futsal athletes of SMA Negeri Olahraga, Riau Province. Materials and methods. This study research is descriptive research that provides an overview of the object studied, the method used is a survey method using questionnaires as instruments. The population in this study was 15 futsal athletes of SMA Negeri Olahraga, Riau Province. The sample was taken as a whole from the study population or total sample. Results. The results of this study are about the picture of the level of knowledge of high nutrition, shown by those who fall into the very high category 1 (6.7%), high category 13 (86.7%), sufficient category 1 (6.7%), and low category. The food consumption pattern of futsal athletes of Riau Provincial Sports State High School seen from the frequency of food use shows that the consumption of staple foods is white rice consumed by more than one athlete a day, side dishes and vegetables are fish, chicken, tofu, tempeh finished more than three athletes per week, vegetables are spinach consumed. Conclutions. It can be concluded that futsal athletes’ nutritional knowledge and consumption patterns need to be improved again because sports nutrition greatly affects the physical activity of athletes in achieving maximum performance.